Aberrant Metabolism as Inductor of Epigenetic Changes in Breast Cancer: Therapeutic Opportunities - Coronel-Hernández, Jossimar; Pérez-Yépez, Eloy Andrés; Delgado-Waldo, Izamary; Contreras-Romero, Carlos; Jacobo-Herrera, Nadia; Cantú-De León, David; Pérez-Plasencia, Carlos (Frontiers in Oncology, 2021)
Evidence about cancer phenotypes indicates that all cancers have in at least eight biological capabilities during the tumor development: sustained proliferation, evasion of growth suppressors signals, resistance to cell death, replicative immortality, angiogenesis, invasion and metastasis, immune-mediated destruction evasion, and reprogrammed metabolism. It has been observed that metabolic rewiring is necessary to produce high levels of energy in order to support the accelerated cell proliferation rates. This metabolic change includes the Warburg effect and alterations in key pathways involved in glutaminolysis, pentose phosphate, and unsaturated fatty acid biosynthesis. Modifications in all these pathways have consequences that impact directly in genetics and epigenetics processes such as DNA methylation patterns, histone post-translational modifications, non-coding RNA expression levels (MicroRNAs and LncRNAs), and chromatin remodeler functions, triggering oncogenes activation and loss in tumor suppressor genes expression to lead the tumor establishment. In this review, we focus to describe the metabolic rearrangement and its association with epigenetic regulation in breast cancer as well its implication in biological processes involved in cancer progression. A better understanding of these processes could help to find new targets for the diagnosis, prognosis, and treatment of this human health problem.